A Study of Learning and Thinking Patterns in Relation to Emotional Intelligence Styles: Exploring the Relationship Between Learning and Thinking Patterns and Emotional Intelligence Styles in Education (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Today's students are expected to play several roles and do so effectively and efficiently,making it imperative that they understand their proper place in society and the need for a greateducation while also developing a passion for learning. By making students more emotionallyintelligent, the proposed New Education Policy aims to improve educational outcomes. EmotionalIntelligence is a type of social intelligence that focuses on the capacity to distinguish between theemotions of one as well as those of others. The brain is where emotions and learning take place. Tolearn is to gain new information or abilities. To learn, you must use your brain. Our ideas have animpact on our emotions. Our thoughts and feelings are intertwined. Academic success can befacilitated for kids who have strong learning and thinking processes as well as high levels of emotionalintelligence. it will assist them in selecting appropriate learning and thinking methods, gaining insightinto their emotional intelligence and attaining their highest academic potential.